WANDERING LETTERS - Costa, Ioana (European Scientific Journal, ESJ, 2014)
The history of printing tightly connects Georgia and Romania: Anthim the Iberian (Metropolitan of Bucharest in 1708-1715), born in Caucasian Iberia, was asked to settle in Wallachia by Prince Constantine BrÃ¢ncoveanu, who entrusted him the newly-founded printing press in Bucharest. His apprentice, Mihail Stefanovici, printed the first Georgian book, accompanied by a dedication to Prince Vahtang VI, written in Romanian language, but with Georgian typeface. This typographic glide, although odd, is consistent with the extensive history of using and adjusting foreign alphabets. Discrepancies that emerged whenever a foreign writing system was borrowed are somehow obliterated by graphic conventions inside each language. Adjustments were made throughout the history of individual languages and only some of the attempts actually survived. Among huge failures in adopting a writing system is to be considered the so called â€œLinear Bâ€, a rudimentary syllabic script that is highly improper for the Greek language. Some other borrowed sets of graphemes were more successful, without ever being completely suitable. Both the Greek and Latin alphabets display adjustments that sometimes have unexpected results when comparing their analogous lists of letters. Phonetic development of Romanian language altered some of the Latin vowels into new phonemes: â€œposterior-iâ€ replaced some previous i, a, e, u or o. A new grapheme was required. Four distinct orthographic reforms (in 1904, 1932, 1953, and 1965) eventually accomplished this task. The beginning of the â€˜90s became a wide-ranging field for change. Orthography turned out to be a target: the regular grapheme Ã® was largely replaced by Ã¢, in a manner that combined different principles (phonetic and etymological), including the position inside the word. In spite of the linguistic requirements, this reform became official in 1993.